ANALYSIS OF THE TRANSFORMATION OF THE NATIONAL INSURANCE MARKET OF UZBEKISTAN - Kenjayev Ilhom Giyozovich; Ganiyev Shahriddin Vokhidovich (Western European Studies, 2024)
This article presents analytical data on collected insurance premiums and insurance payments made for insurance services provided on the national insurance market of Uzbekistan, the amount of liability received, and offers and recommendations.
Keywords: market; Insurer; insured